Anesthetic ointment only (lidocaine/prilocaine) instead of injectable local lidocaine in trans‐radial catheterization: A viable no‐needle alternative. (26th June 2017) - Latsios, George; Toutouzas, Kostas; Antonopoulos, Alexios S.; Melidi, Eleni; Synetos, Andreas; Vogiatzi, Georgia; Stasinopoulou, Aggeliki; Tsioufis, Kostas; Tsiamis, Eleftherios; Tousoulis, Dimitrios
Abstract : Objective: The aim of the present study was to assess the level of access site pain in patients undergoing transradial coronary catheterization by using topical application of an anesthetic ointment (lidocaine/prilocaine—AO) compared to standard local anesthesia (LA) by means of injectable lidocaine. Methods: We prospectively studied 444 patients undergoing elective trans‐radial coronary angiography. The quality of analgesia was assessed using a visual analogue scale (VAS) immediately after the puncture and 30 min after the removal of the sheath. The number and duration of attempts before successful sheath insertion, as well as artery spasm, were compared between the two groups. Results: Pain levels measured by VAS were found to be similar between the two groups during sheath insertion (VAS: AO: 4.84 ± 1.0 vs 4.82 ± 1.2, P = NS), as well as 30 min after sheath removal (VAS: AO: 0.07 ± 0.5 vs LA: 0.15 ± 0.6, P = NS). The time to obtain radial access was also not affected by the use of anesthetic ointment (AO: 62.24 ± 25.7 s vs LA: 64.04 ± 18.78 sec, P = NS). The rate of clinical or angiographic radial artery spasm was similar (8‐10%) between the groups ( P = NS) Conclusion: Use of a local anesthetic ointment, versus injectable lidocaine, in trans‐radial cardiac catheterization as means of local anesthesia, was found to be equally effective in terms of pain, artery spasm, or artery cannulation speed.